2009
DOI: 10.3382/ps.2008-00433
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of glycine, total sulfur amino acids, and lysine supplementation to corn-soybean meal diets on growth performance and serum uric acid and urea concentrations in broilers

Abstract: Four experiments were conducted to determine the interactive effects of Gly, TSAA, and Lys in corn-soybean meal diets on growth performance of broilers. All experiments were conducted with female Ross x Ross 308 or 708 broilers in brooder batteries from 0 to 18 d posthatching. Treatments had 5 to 8 replications with 5 or 6 broilers per replicate pen. Diets in all experiments were fed without or with Gly (2.32% total Gly + Ser). All diets contained 0.25% l-Lys.HCl except in experiment 1, where no crystalline Ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Alternatively, Gly fortification reduced urea production by inhibiting arginase activity (Austic and Nesheim 1970). Similar to the previous studies (Powell et al 2009;Awad et al 2017;Law et al 2018), we observed a reduction of serum UA content on d 42 with dietary CP reduction by 4.5% or 6%, which could be related to the lower ingestion with the subsequent reduced catabolism of AA (Awad et al 2017;Law et al 2018). Although Gly is directly involved in the synthesis of UA, we did not find an alteration of serum UA content in response to Gly fortification in the low-CP diets, which did not agree with the study of Awad et al (2017).…”
Section: Discussionsupporting
confidence: 87%
“…Alternatively, Gly fortification reduced urea production by inhibiting arginase activity (Austic and Nesheim 1970). Similar to the previous studies (Powell et al 2009;Awad et al 2017;Law et al 2018), we observed a reduction of serum UA content on d 42 with dietary CP reduction by 4.5% or 6%, which could be related to the lower ingestion with the subsequent reduced catabolism of AA (Awad et al 2017;Law et al 2018). Although Gly is directly involved in the synthesis of UA, we did not find an alteration of serum UA content in response to Gly fortification in the low-CP diets, which did not agree with the study of Awad et al (2017).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, improvement in ether extract digestibility has been associated with supplemental glycine in the diet (Han & Thacker, ). Betaine improves the availability of glycine (Eklund et al, ), which conjugates with bile acids synthesized in the liver to form bile salts (Powell, Bidner, & Southern, ). In addition, higher levels of short‐chain fatty acids along the intestinal tract may improve the absorption capacity of the intestinal epithelium, leading to an improved digestive capacity (Butzner et al, ).…”
Section: The Effects Of Betaine On Nutrient Digestibilitymentioning
confidence: 99%
“…Hilliar et al (2019) showed that reducing crude protein significantly decreased serum uric acid by 26.9%. Moreover, Powel et al (2009) observed that glycine addition to broiler chick diets decreased serum uric acid and serum urea N concentrations.…”
Section: Blood Metabolites and Antioxidant Statusmentioning
confidence: 96%
“…Moreover, Awad et al (2018) showed that feeding birds with low protein diet fortified with glycine 0.8 -1% of diets resulted in feed consumption, weight gain and feed conversion ratio equivalent to the broiler chicks fed normal protein diets, as well as improved protein efficiency. In addition, Powel et al (2009) indicated that glycine addition to broiler chick diets increased feed efficiency in diets with 1.35% lysine and excess total sulphur amino acids. Chrystal et al (2020) indicated that inclusions of glycine and threonine in the 16.5% protein diet resulted in 6.18% increase in ileal protein digestibility coefficients and 10.1% increase in ileal protein disappearance rates.…”
Section: Introductionmentioning
confidence: 99%